Milenial Parents' Parenting Patterns are in Danger Use of Early Children's Gadgets - Ramandhani, Dyah Fitri; Arbarini, Mintarsih; Loretha, All Fine (Universitas Pendidikan Ganesha, 2023)
Parenting influences early childhood gadget use. This study aims to analyze the parenting style of millennial parents regarding the dangers of using early childhood gadgets in the Tunggulrejo Village, Gabus District, Grobogan Regency. This research was conducted using observation, interviews, and documentation of five research subjects for the data collection process. The method of data analysis is carried out directly based on the results of field work, namely data collection, data reduction, data presentation, and drawing conclusions. The results of this study indicate that children with this parenting style become independent and have good creativity, permissive parenting style gives freedom to children without reprimands and punishments, even though children make mistakes. In this study, the parenting style that is mostly applied by millennial parents in using gadgets for children aged 3-6 years in the Tunggulrejo Village tends to use permissive parenting. The negative impacts of using early childhood gadgets in Tunggulrejo Village are eye health problems, children get angry easily, children prefer to be alone, and children are more lazy in doing things. This research is expected to be useful in developing knowledge in the field of education, especially in terms of early childhood care. Furthermore, this research is expected to be the basis of reference for further studies that have related topics.